ENACTED SENSEMAKING IN CRISIS SITUATIONS[1] - Weick, Karl E. (Journal of Management Studies, 1988)
ABSTRACTSensemaking in crisis conditions is made more difficult because action that is instrumental to understanding the crisis often intensifies the crisis. This dilemma is interpreted from the perspective that people enact the environments which constrain them. It is argued that commitment, capacity, and expectations affect sensemaking during crisis and the severity of the crisis itself. It is proposed that the core concepts of enactment may comprise an ideology that reduces the likelihood of crisis.